Why shouldn't we cut the human-biosphere umbilical cord?. (October 2021) - Holt, Lauren Adele
Highlights: An extreme technologically adapted future has not been defined in the literature. Such a future could be argued to be morally justifiable. However, a highly technologically mediated relationship with the biosphere introduces unique risks. These are likely to endanger humanity and future Earth-originating life-forms as well as creating moral hazard. An extreme technologically adapted future is therefore undesirable compared to restabilising the biosphere. Abstract: Scientific and technological advancements have made many wonderful things possible for humankind. As these continue to develop, civilization may evolve to a stage of technological maturity where humanity could, not merely survive, but flourish under the harshest possible environmental conditions, including those off-planet. Even now, aided by seedbanks and underground bunkers, small pockets of humans have never been better prepared to survive a severe environmental global catastrophe through decoupling from the biosphere. This paper explores the moral desirability of extensive technologically-separated civilizations and, if they are achieved, what our relationship might be to the remaining ecological environment. The paper begins by exploring several visions of techno-adaptation and their appeal before laying out the moral arguments in their favour. I then explore the ways that an extensive technologically mediated, or highly-separated relationship with the biosphere is inherently risky and is likely to endanger an independently functioning biosphere — which has its own intrinsic value. I conclude that humanity should preserve the independence of natural processes and achieving material decoupling cannot justify eroding or damaging the remaining biosphere. Thus, given a choice, cutting the human-biosphere 'umbilical cord' is morally undesirable unless done in the service of reducing negative impacts on the biosphere.